Epidemiology of fragile skin: Internet-based surveys in Mexico and Russia - Ocampo Candiani, Jorge; Murashkin, Nikolay; Zkik, Asmaa; Saint Aroman, Markéta; Wolkenstein, Pierre (2017)
Background: Fragile skin is a poorly understood skin condition, particularly in the general adult population. There are currently limited epidemiological data on the prevalence of fragile skin in adults. The objectives of this study were to assess the prevalence of perceived fragile skin across different skin types in representative samples of the general adult populations in Mexico and Russia, and to identify skin characteristics associated with perceived fragile skin. Methods: Two identical cross-sectional surveys, using a short online self-administered questionnaire, were conducted on samples of recruited individuals that were representative of the general Mexican and Russian populations. Participants responded to questions about fragile skin, with the main question being “In your opinion, do you have fragile skin (ie, skin less resistant and reacting quickly to external aggressions)?”. The survey also covered questions relating to skin appearance, skin symptoms, skin disease, dermatological procedures, and living environment and climate. Results: Overall, 1,210 individuals in Mexico (N=606) and Russia (N=604) completed the online survey. Fragile skin was perceived in 50.0% and 45.9% of participants in Mexico and Russia, respectively. The principal skin appearance characteristics reported by individuals with perceived fragile skin were thin, easily wrinkled, and transparent; the main skin symptoms were dryness, redness, and/or itching (≥50% of individuals in Mexico), and dryness, tightness, and/ or redness (>60% of individuals in Russia). Individuals with perceived fragile skin had experienced skin disease and/or undergone a dermatological procedure in the past 12 months, and they reported being exposed to stress (>80% of individuals in both surveys). Conclusion: A substantial proportion of the general adult population of Mexico and Russia perceived that they had fragile skin, regardless of their skin type; fragile skin was perceived more frequently in women. These findings should assist dermatologists to extend their understanding and management of individuals with perceived fragile skin. Keywords: epidemiology, fragile skin, prevalence, skin type, survey